Elevated peripheral glutamate and upregulated expression of NMDA receptor NR1 subunit in insomnia disorder - Lin, Jingjing; Hou, Xiaohui; Liu, Yaxi; Cai, Yixian; Pan, Jiyang; Liao, Jiwu (Frontiers in Psychiatry, 2024)
Background: The present study explored the serum glutamate (Glu), glutamine (Gln), glutamic acid dehydrogenase (GAD) concentrations and the mRNA expression levels of the N-methyl-D-aspartate receptor (NMDAR) NR1 subunit in the peripheral blood of patients with insomnia disorder (ID). To our knowledge, this is the first study showing an increase in the mRNA expression levels of the NMDAR NR1 subunit in patients with ID. Methods: This study included 30 ID patients and 30 matched healthy controls. We investigated the demographic and illness information and assessed subjective sleep quality using the Pittsburgh Sleep Quality Index. The Hamilton Depression Scale-17 and Hamilton Anxiety Scale were used to evaluate the patients’ symptoms of depression and anxiety, respectively. The quantifications of Glu, Gln and GAD concentrations were performed by Enzyme-linked immunosorbent assay (ELISA). Real-time PCR was used to detect the mRNA expression levels of the NMDAR NR1 subunit in peripheral blood. Results: Compared with the healthy control group, the serum Glu concentrations and the mRNA expression levels of the NMDAR NR1 subunit in the ID group were significantly higher. However, there was no significant difference in Gln and GAD between the two groups. The receiver operating characteristic (ROC) analysis showed that the mRNA expression levels of the NMDAR NR1 subunit could distinguish ID patients from healthy individuals (area under the curve: 0.758; sensitivity: 73.3%; specificity: 76.7%). A negative correlation was found between the mRNA expression levels of the NMDAR NR1 subunit for age, total duration of illness, and age of first onset in the ID group, whereas a positive correlation was detected for daytime dysfunction. Conclusion: Glutamatergic neurotransmission was abnormal in ID patients. Additionally, the mRNA expression levels of the NMDAR NR1 subunit appeared to have potential as a clinical biomarker for ID. However, the sample size of our study was limited, and future studies with larger sample sizes are needed to further validate and explore the mechanisms involved and to assess the reliability of the biomarker.